A New Nonlinear Active Disturbance Rejection Control for the Cable Car System to Restrain the Vibration - Xinyan Hu; Lina Li (Complexity)
The safety of the cable car system is very important for the lives of the people. But, it is easily affected by the environment such as the wind which causes the cable car system to have strong vibration disturbance, thus degrading the safety of the cable car system. In this paper, a new nonlinear active disturbance rejection control (ADRC) is proposed to restrain the vibration of the cable car. First, a new two-mass-spring system model is utilized to establish the cable car system model. The new translation vibration nonlinear model is derived by a linear-invariant two-mass-spring system. Then, a special nonlinear fal• is designed to restrain the vibration, and a new high-order nonlinear ADRC is presented for the cable car system. Finally, simulation results verify the feasibility and accuracy of the proposed model.